Um modelo de planejamento estratégico de sistemas de informação para organizações que atuam em desenvolvimento distribuído de software - Cibotto, Rosefran Adriano Gonçales (2009)
Several organizations that develop software have chosen to create the software or some part of it by teams located in different places. Known as distributed software development (DSD), this approach of work provides recognized benefits among which are skilled and cheap labor, proximity to the customer, productivity gain and advantage of the local law. However, when choosing the DSD, several difficulties related to cultural, psychological, behavioral, communication and organization issues should be addressed. One way of such organizations to protect themselves from the problems of distribution is through the development of a strategic plan. This thesis presents a model of strategic planning of specific information systems to support the DSD which helps to manage distributed teams, to prevent problems arising from the distribution and help to fix them, if they occur. The strategic planning model proposed consists of four steps: 1) management of distributed teams, where the human resources and the social, psychological and cultural aspects are addressed, 2) standardization, issues of infrastructure, technical and legal in which are actions of infrastructure teams and of law, 3) virtual and face meetings, this step, which defines the procedure adopted for the meetings, and, 4) document management, which addresses the management of electronic documents. A scenario for applying the model was developed and was the creation of a strategic plan for the development of a system with distributed teams in Brazil and Angola, which allowed for an evaluation of the model. The evaluation results indicate the importance of this strategic planning model developed in order to address the specificities of the DSD.